Multidrug-Resistant Disseminated Nocardia Farcinica Infection in a Systemic Lupus Erythematosus Patient - Öztürk ATEŞ; Havva CİLAN and Sema OYMAK and Orhan YILDIZ and Oktay OYMAK1 (Archives of Rheumatology, 2013)
Herein, we present a 40-year-old female case who was admitted to our hospital with the complaints of fever and a painful left leg. She had a five-month history of treatment with azathioprine and prednisolone for lupus nephritis. The patient was diagnosed with disseminated nocardiosis (nodular cutaneous lesions, bacteremia, brain abscesses, and a reticulonodular miliary tuberculosis-like infiltration) associated with Nocardia farcinica and was treated using linezolid, netilmicin, and ceftriaxone. This case is important as treatment of Nocardia infections remains week particularly when they involve the central nervous system and when they are sustained by highly drugresistant species such as Nocardia farcinica.